The Importance of Lumbar Curve Flexibility and Apical Vertebral Rotation for the Prediction of Spontaneous Lumbar Curve Correction in Selective Thoracic Fusion for Lenke Type 1 and 2 C Curves: Retrospective Cohort Study with a Mean Follow-Up of More than 10 years. Issue 7 (September 2022) - Kaya, Ozcan; Kara, Deniz; Gok, Halil; Kahraman, Sinan; Sanlı, Tunay; Karadereler, Selhan; Enercan, Meric; Hamzaoglu, Azmi
Study Design: Retrospective analysis of a prospectively collected data. Objective: Lumbar flexibility(LF) is generally defined with preoperative side bending films;it is not clear what percentage of LF predicts the spontaneous lumbar curve correction (SLCC) at long term follow up. Aim of this study was to find out cut-off value of preoperative LF, apical vertebra rotation(AVR) and apical vertebral translation(AVT);which may predict more than 50%SLCC. Methods: Patients with Lenke 1C&2C curves, treated with posterior STF, with a minimum 10 years follow up were included.The patients who had more than 50% SLCC(Group A) or less than 50% (Group B) were compared in terms of LF, AVR and AVT to understand a cut-off value of those parameters.Statistically, Receiver Operating Characteristic(ROC) test was used. Results: Fifty five AIS patients (54F, 1M) with mean age 14 (11-17) were included to study.Thoracic curve correction rate was 75%;lumbar curve correction rate was 59% at the latest follow up.Group A included 45(82%) patients at the latest follow up.Three patients (5%) showed coronal decompensation at early postop and 2 of them became compensated at f/up.ROC analyses showed 69% flexibility as the cut-off value for SLCC ( P < .01).The difference between groups in terms of preop mean AVRs was significant ( P = .029) (Group A = 1.9; Group B = 2.4). Conclusion: In Lenke 1C&2C curves, whenever LF on the preoperative bending x-ray is greater than 70% ( P < .01)and AVR is equal or less than grade 2, STF provides satisfactory clinical and radiological SLCC with more than mean 10 years f/up.This flexibility rate and apical vertebral rotation can be helpful in decision making for successful STF.